2021
DOI: 10.21037/tlcr-21-461
|View full text |Cite
|
Sign up to set email alerts
|

Impact of tumor programmed death ligand-1 expression on osimertinib efficacy in untreated EGFR-mutated advanced non-small cell lung cancer: a prospective observational study

Abstract: Background: Osimertinib monotherapy is currently the standard of care as a first-line treatment for patients harboring epidermal growth factor receptor (EGFR) mutations; however, some EGFR-mutated non-small cell lung cancer (NSCLC) patients exhibit primary resistance and an insufficient response to EGFR-tyrosine kinase inhibitors (EGFR-TKIs). Elevated programmed death-ligand 1 (PD-L1) expression in tumors was reported as a negative predictive factor for outcomes of first-or second-generation EGFR-TKIs.Methods:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 48 publications
2
19
0
Order By: Relevance
“…Previous studies have reported PD-L1 TPS <1% in 42.4%-62.7%, 1%-49% in 25.55%-37.6%, and ≥ 50% in 9.4%-21.2% of lung adenocarcinoma patients. 15,23,33 PD-L1 TPS in this study was 49.2% for <1%, 29.5% for 1%-49%, and 21.3% for ≥50%, similar to previously reported results.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Previous studies have reported PD-L1 TPS <1% in 42.4%-62.7%, 1%-49% in 25.55%-37.6%, and ≥ 50% in 9.4%-21.2% of lung adenocarcinoma patients. 15,23,33 PD-L1 TPS in this study was 49.2% for <1%, 29.5% for 1%-49%, and 21.3% for ≥50%, similar to previously reported results.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have reported PD‐L1 TPS <1% in 42.4%–62.7%, 1%–49% in 25.55%–37.6%, and ≥ 50% in 9.4%–21.2% of lung adenocarcinoma patients. 15 , 23 , 33 PD‐L1 TPS in this study was 49.2% for <1%, 29.5% for 1%–49%, and 21.3% for ≥50%, similar to previously reported results. The association between PD‐L1 TPS and therapeutic efficacy of first/second generation EGFR‐TKIs have been reported in many studies, with patients with PD‐L1 TPS ≥50% reported to have lower objective response rate, shorter PFS, and more de novo resistance compared to those with TPS < 50%.…”
Section: Discussionsupporting
confidence: 92%
“…Several previous studies showed that EGFR-mutated advanced NSCLC with high TPS had poorer treatment outcomes with first-or second-generation EGFR-TKI compared with the weak or negative PD-L1 population [12,13]. Regarding osimertinib, a recent study of 71 patients who received first-line osimertinib revealed that patients with ind PD-L1 expression had poorer PFS than those with low or negative PD-L1 (median PFS, 5.0 vs. 17.4 months, p < 0.001) [14]. The present study demonstrated similar results in a larger sample size.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, immune‐checkpoint inhibitors (ICIs) are generally less effective in NSCLC patients harboring driver mutations, such as EGFR and ALK 22,23 . Elevated PD‐L1 expression in tumors is reportedly a negative predictive factor for EGFR‐TKI outcomes in NSCLC patients with EGFR mutations 24–26 …”
Section: Introductionmentioning
confidence: 99%
“… 22 , 23 Elevated PD‐L1 expression in tumors is reportedly a negative predictive factor for EGFR‐TKI outcomes in NSCLC patients with EGFR mutations. 24 , 25 , 26 …”
Section: Introductionmentioning
confidence: 99%